Analysis of Followers Buying Interest in the @Itsmekaia Instagram Account using the Elaboration Likelihood Model Theory - Nuriyati Samatan; Marwan Londol; Robingah; Jun Firmansyah; Ludofika Pradnya Diva Kintani (Siber International Journal of Digital Business (SIJDB), 2025)
Abstract: This research aims to measure the effect of Credibility (Variable X1); Celebrity Endorser (Variable X2) on the Followers' Buying Interest (Variable Y). The object of research is the @itsmekaia Instagram account using the Elaboration Likehood Model theory.The type of research is quantitative, with a Positivistic paradigm. The object of research is the Instagram account @ itsmekaia, the research subject is the followers on the Instagram account @itsmekaia, which is selected according to predetermined criteria. This research uses non probability sampling technique with purposive sampling method. Determination of the sample size using the Slovin Formula, with a margin of error of 0.5%, the number of respondents is 400.The results of the research involving 400 respondents showed through the Ftest (simultaneous) that Ho3 was rejected and Ha3 was accepted with a calculated Fvalue of 222.146 greater than 3.018 ftable. This showed a significant relationship between message credibility and celebrity endorser credibility on purchase intention. Analysis using the Elaboration Likelihood Model showed that the persuasive message process through credibility and Celebrity Endorser, called the Middle Path, had an effect on followers' purchase intention. The results also showed that the Middle Path jointly influences through the Periphery Path, when persuasive messages attract followers through the appearance, language and gestures of celebrity endorsers.